Influencia del programa “Juego de roles”, para desarrollar habilidades sociales en los niños de 3 años de la I.E.P. Villasol – 2017 - Saucedo Fernandez, Gisela (2020)
The present piece of pre-experimental research aims to determine to what extent the Role-play Program influences on the development of 3-year-old children’s social skills in the I.E.P. Villasol during the year 2017._x000D_ The Role-play Program was aimed at developing social skills, so that the 3-year-old children acquire them in a spontaneous way, following the right sequence and without helping or supervision, according to the situation they face._x000D_ To carry out this study, an observation guide was used as a data collection instrument, taking into account 6 evaluation criteria. It was conducted in 20 learning sessions by using various materials and it was found that 93.30% of the children got to achieve significant development of social skills._x000D_ The statistically obtained results show that the children's social skills level was low before the intervention and how it developed after applying the Role-play Program as it can be seen on the tables presented in the results. We can conclude that the application of the Role-Play Program did have a significant influence on the development of 3-year-old children’s social skills in the I.E.P. Villasol during the year 2017.